Flow boiling in expanding microchannels - Alam, Tamanna (Springer, 2017)
This Brief presents an up to date summary of details of the flow boiling heat transfer, pressure drop and instability characteristics; two phase flow patterns of expanding microchannels. Results obtained from the different expanding microscale geometries are presented for comparison and addition to that, comparison with literatures is also performed. Finally, parametric studies are performed and presented in the brief. The findings from this study could help in understanding the complex microscale flow boiling behavior and aid in the design and implementation of reliable compact heat sinks for practical applications.
Keywords: Ebullition.; Microreactors.; elektronické knihy; electronic books